Methods to improve innovative activities as prior areas for development of the region - Шеденов, У.; Шеденова, Н.; Елтай A. (Journal of Economic Research & Business Administration, 2018)
In this paper, the theoretical principles of increasing the effectiveness of public administration and practical recommendations in the socio – economic development trend are presented to ensure sustainable economic development of the regions of the Republic of Kazakhstan. There are also proposed ways of optimization and development by identifying and analyzing the main problems of regional governance in the Republic of Kazakhstan. The main problem is to improve the social and economic situation of the regions by developing innovative activities in the development of these regions. There are some obstacles to innovation in the regions and this article presents ways to solve these obstacles. For Kazakhstan, a state regional policy aimed at aligning the trend of socio-economic development is important from a strategic point of view. Sustainable development of the national economy is not possible without improving living conditions in the problematic regions of the country. The current economic space of the republic covers various regions characterized by social, economic, environmental and special problems. The aim of the study is an innovative solution of problems in the regions. Therefore, on the threshold of economic global trends for Kazakhstan, the main task that needs solutions is to neutralize the negative consequences for the regions and to formulate the conditions necessary for their development, which will allow to increase the positive result.